2021
DOI: 10.1101/2021.03.26.437144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic analysis of response to neoadjuvant chemotherapy in esophageal adenocarcinoma

Abstract: Neoadjuvant therapy followed by surgery is the standard of care for locally advanced esophageal adenocarcinoma (EAC). Unfortunately, response to neoadjuvant chemotherapy (NAC) is poor (<20%), as is the overall survival benefit at 5 years (5%). The EAC genome is complex and heterogeneous between patients, and it is not yet understood whether specific mutational patterns may result in chemotherapy sensitivity or resistance. To identify associations between genomic events and response to NAC in EAC, a comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(122 reference statements)
1
2
0
Order By: Relevance
“…The mutational landscape of these OAC patients described by WES is consistent with previous characterizations of high mutational burden [14], mutational signatures with high proportions of C > T substitutions and evidence of chromosomal instability [4, 5, 21]. Gene expression analysis estimating the populations of infiltrating lymphocytes indicated that mutations yielding neoantigens may be detectable.…”
Section: Discussionsupporting
confidence: 83%
“…The mutational landscape of these OAC patients described by WES is consistent with previous characterizations of high mutational burden [14], mutational signatures with high proportions of C > T substitutions and evidence of chromosomal instability [4, 5, 21]. Gene expression analysis estimating the populations of infiltrating lymphocytes indicated that mutations yielding neoantigens may be detectable.…”
Section: Discussionsupporting
confidence: 83%
“…32 Amplification and mutation of KRAS have been previously reported in EAC. 30,54,55 Despite the mutation frequency of KRAS in EAC being less than 20%, it is considered an EAC driver and proposed targeting of KRAS mutations may sensitize a subgroup of EAC patients to targeted treatment. 30 Alternative splicing of KRAS is well documented in other cancers, 33,35,[56][57][58][59][60] resulting in two isoforms, KRAS4A and KRAS4B, 33 both of which can carry KRAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EGFR tyrosine kinase inhibitors block the abnormal signal transduction of EGFR and tyrosine kinase and induce apoptosis, thereby inhibiting the growth of tumor cells. EGFR tyrosine kinase inhibitors produce resistance via mechanisms such as EGFR mutations (17). Further, proteoglycans, as a sort of extracellular matrix in the tumor microenvironment, regulate the biological behavior of tumor cells via metabolic processes (18).…”
Section: Discussionmentioning
confidence: 99%